Analisis Kawasan Rawan Bencana Longsor dan Mitigasi di Kecamatan Padang Selatan - Ibrahim, Malik; Triyatno, Triyatno (TSAQOFAH, 2025)
South Padang District has varied topography with steep slopes, making it prone to landslides, particularly during the rainy season. This vulnerability is exacerbated by uncontrolled land-use changes, necessitating a comprehensive study to map hazard-prone areas and formulate mitigation strategies. This study aims to: (1) model landslide-prone areas in South Padang District using the Frequency Ratio (FR) method and (2) determine priority mitigation efforts using the Analytical Hierarchy Process (AHP) method. A descriptive quantitative approach was applied, with the FR method used to analyze hazard levels and AHP employed to establish mitigation strategy priorities. The analysis results indicate three hazard categories: low (26%, 208,524 pixels), medium (34%, 266,624 pixels), and high (40%, 379,864 pixels) of the total area. AHP analysis using Expert Choice placed landslide hazard mapping as the top priority with a weight of 0.376. These findings emphasize that spatial approaches and land-use control should form the basis for effective, targeted, and sustainable landslide mitigation policies.